Analisis Penggunaan Gaya Bahasa pada Puisi Karya Siswa Kelas VII SMP Negeri 1 Sanana - Sarmina Ati; Siti Fariza Soamangun (Jurnal Ilmiah Wahana Pendidikan, 2023)
The style of language in a work such as poetry has a beautiful effect so that the poem becomes more attractive and increases the reader's taste. This study aims to describe the use of language style in poetry by students in Class VII of SMP Negeri 1 Sanana. Research is a type of qualitative research. The subject of this study was poetry written by class VII students of SMP Negeri 1 Sanana. There were 34 student works that were used as research subjects, according to the number of students in class VII of SMP Negeri 1 Sanana. This research was conducted at SMP Negeri 1 Sanana. The instruments used in this research consist of: 1) the researchers themselves (human instruments); 2) Data card; and 3) Data Classification Sheet. The data analysis technique in this study uses semantic analysis, namely by reading, translating poetry seriously, and classifying data into figurative language according to existing theories. The data were then analyzed for style and grouped according to Keraf and Tarigan's style theory. The results of this study indicate that there are 10 types of figurative language contained in the 34 poetry works of students of SMP Negeri 1 Sanana analyzed in this study. The most common classification of language style used in poetry works by class VII students of SMP Negeri 1 Sanana is comparative language style, with the most widely used type of language style being personification language style reaching 53 uses..